The hierarchical model of branch planning with random coefficients - Silva, Geraldo Nunes [UNESP]; Treskov, Y. P.; Tsurkov, VI (Maik Nauka/interperiodica, 1998)
We consider the management branch model where the random resources of the subsystem are given by the exponential distributions. The determinate equivalent is a block structure problem of quadratic programming. It is solved effectively by means of the decomposition method, which is based on iterative aggregation. The aggregation problem of the upper level is resolved analytically. This overcomes all difficulties concerning the large dimension of the main problem.